2018
DOI: 10.7150/thno.23209
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular MMPs efficiently inhibits tumor metastasis and angiogenesis

Abstract: Treatment for metastatic cancer is a great challenge throughout the world. Commonly, directed inhibition of extracellular matrix metalloproteinases (MMPs) secreted by cancer cells can reduce metastasis. Here, a novel nanoplatform (HPMC NPs) assembled from hyaluronic acid (HA)-paclitaxel (PTX) prodrug and marimastat (MATT)/β-casein (CN) complexes was established to cure a 4T1 metastatic cancer model via targeting CD44 and intracellular, rather than extracellular, MMPs.Methods: HPMC NPs were prepared by assembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…On the other side, we found that the inhibition efficacy in metastasis from nanoparticle formulation was markedly different from that of the free drug, despite that their discrepancy of MMP inhibition in vivo was less than 20% (Figure ) . In this study, MATT‐LTSLs enabled threefold of metastasic nodules less than the free MATT (Figure c,d), being in line with our previous reports . Therefore, we speculate that abundant MMPs exist in the tumor site; and as a result, effective delivery of MATT to the tumor site with carriers is indispensable.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…On the other side, we found that the inhibition efficacy in metastasis from nanoparticle formulation was markedly different from that of the free drug, despite that their discrepancy of MMP inhibition in vivo was less than 20% (Figure ) . In this study, MATT‐LTSLs enabled threefold of metastasic nodules less than the free MATT (Figure c,d), being in line with our previous reports . Therefore, we speculate that abundant MMPs exist in the tumor site; and as a result, effective delivery of MATT to the tumor site with carriers is indispensable.…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, recent studies unveiled that the drug could inhibit the metastasis, alleviate the inflammation, and regulate the immune system via inhibition of MMPs. Indeed, our previous reports indicated the drug blocked the metastasis significantly . On the other side, we found that the inhibition efficacy in metastasis from nanoparticle formulation was markedly different from that of the free drug, despite that their discrepancy of MMP inhibition in vivo was less than 20% (Figure ) .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations